Penapisan Bakteri Simbion Gastropoda Stramonita armigera Penghasil Senyawa Antibakteri Multi Drug Resistant dari Perairan Ternate - Pringgenies, Delianis; Dananjoyo, Mijil Ciptaning (Jurnal Natur Indonesia, 2011)
Antibiotic resistance is an ability of bacteria to hold the antibiotic effect. It was reported that there is a human-patogen bacteria that resistance to one or more classes of antibiotic. It become a problem on medical world. Tosolve those problems, it is necessary to search the new antibiotic compounds that more effective and efficient tosolve the problem of Multi Drug Resistance (MDR). The secondary metabolite-producing marine invertebrates andsymbiont microorganisms, have prospect as an antibiotic. The symbiont microorganisms may produce thesecondary metabolite similar to their host. The aims of the reseach were to determinate of gastropods symbiontbacteria that capable of producing Antibacterial MDR (Multi Drugs Resistant) Compound. Sample of Molusc werecollected from Ternate (Molucas) islands. Isolation of symbiotic bacteria, screening for bacteria which producingsecondary metabolites as anti-MDR bacteria, antibacterial test, isolation of clinical pathogenic bacteria (MDR),conducting anti-bacterial sensitivity test, sensitivity test for antibacterial, DNA exctraction, DNA amplificationbased on PCR method, DNA sequencing. Result of 16S r-DNA sequence was then analyzed and edited usingGENETYX program and followed by 16S rDNA sequence analysis. The result showed that 17 strains were isolatedfrom gastropods Stramonita armigera. Antibacterial assays showed that TSA 8.7 isolate have ability to inhibitPseudomonas sp., Escherichia coli dan Enterobacter sp. the molecular analyses showed that isolate TSA 8.7closed by related to Vibrio sp. Strain JZDN1, with 98% of homology. Based on this experimental result, it could beconcluded that gastropods-symbiont bacterium Stramonita armigera capable of producing antibacterial compoundagainst strain Multi Drug Resistant (MDR). There is 11 isolates of gastropods-symbiont bacteria Stramonita armigerathat have an antibacterial MDR activity.